Stainless steel crowns reuse and decontamination techniques: A survey among Indian pediatric dentists - K Farhin; S Abhinav; P Thejokrishna; M Sajjad (Wolters Kluwer Medknow Publications, 2013)
Objective: To determine the pattern and extent of stainless steel crown (SSC) reuse following try-in and the methods employed for their decontamination among Indian pediatric dentists. Study Design: Questionnaires were delivered personally to 100 pediatric dentists selected randomly across India. Questionnaire was divided into three subsections. The first section assessed demographics to determine the sample population characteristics. The second section dealt with the pattern of SSCs use and reuse following size determination. The third section inquired into general cross infection control procedures including cleaning, sterilization, and training to assess the general level of compliance. Data analysis involved descriptive analysis using SPSS 16.0 software. Results: The majority of respondents (98.92%) routinely reused the crowns after they had been tried in the patient. Only one respondent (1.08%) discarded the crowns after try-in. Autoclave (25%) was the most common method employed for the decontamination of tried-in SSCs among the respondents. Conclusion: The majority of the participating pediatric dentists are reusing SSCs following try-in during crown selection. However, great diversity exists in the methods employed for the decontamination of the same. This demands for more research to provide guidelines into the most effective method of decontamination.